2013
DOI: 10.1049/iet-ipr.2013.0008
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and localisation of whole slide images using unsupervised learning

Abstract: Digital pathology has been clinically approved for over a decade to replace traditional methods of diagnosis. Many challenges appear when digitising the whole slide scan into high resolution images including memory and time management. Whole slide images require huge memory space if the tissue is not pre-localised for the scanner. The authors propose a set of clinically motivated features representing colour, intensity, texture and location to segment and localise the tissue from the whole slide image. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Neither the 8 images nor their tissue-staining categories were used for training or validation of the Full results are presented in Table 7. We did not include the published tissue segmentation method by Hiary et al (Hiary et al, 2013) in this study: They reported their results as a localization error in which a pathologist partly determined which errors were relevant (and thus counted), making the approach irreproducible for us. Re-implementing this method was not feasible due to missing algorithmic details.…”
Section: Results On the Dissimilar Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the 8 images nor their tissue-staining categories were used for training or validation of the Full results are presented in Table 7. We did not include the published tissue segmentation method by Hiary et al (Hiary et al, 2013) in this study: They reported their results as a localization error in which a pathologist partly determined which errors were relevant (and thus counted), making the approach irreproducible for us. Re-implementing this method was not feasible due to missing algorithmic details.…”
Section: Results On the Dissimilar Datasetmentioning
confidence: 99%
“…Manuscript to be reviewed et al, 2015); the result is subsequently refined via flood filling from identified background points. Hiary et al built a different algorithm based on k-means clustering using pixel intensity, color, and texture features (Hiary et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We did not directly compare to the other published tissue segmentation methods by Hiary et al [3]. They report their results as a localization error in which a pathologist partly determined which errors were relevant (and thus counted), making the approach irreproducible for us.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, there is no single segmentation method with acceptable results for all medical imaging modalities [ 9 ]. According to that challenge, medical imaging segmentation remains a problem for this field [ 11 ]. There are different approaches in medical image segmentation with some approaches based on heuristics, region growing, edge detection, and thresholding methods [ 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…The problem of localizing the focus point regions from the whole-slide tissue image can be addressed as a clustering problem in image processing [ 9 , 11 13 ]. Our objective in this paper is to propose an adaptive localization method for Ki-67 staining of whole-slide tissue for histology images of a brain tumor.…”
Section: Introductionmentioning
confidence: 99%